Simulation Study on the Development Process and Phase Interface Structure of Gas-Liquid Slug Flow in a Horizontal Pipe - Wu, Xiao; Wang, Zhaoting; Dong, Mei; Ge, Quan; Dong, Longfei (Frontiers in Energy Research, 2021)
The problems of high pressure drop, system resonance, and the difficulty of terminal gas-liquid treatment caused by slug flow have prompted in-depth research on this flow pattern. Here, a unified 3D numerical model of gas-liquid two-phase flow in a horizontal pipe was established using the interface capture method based on the open source software package OpenFOAM. Through numerical simulation of the natural slugging and development process of slug flow under different working conditions, the motion, phase interface structure, and pressure and velocity field distributions of the liquid slug were analyzed and fully developed. The simulation results are in good agreement with the experiment. The results showed that during the movement of the slug head, there is a throwing phenomenon and a wave-like motion of the liquid slug.